2002
DOI: 10.1097/00006454-200201000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Courses of Croup Caused by Influenza and Parainfluenza Viruses

Abstract: Influenza viruses have occasionally been associated with severe manifestations of croup, but no comparative studies of different viral etiologies are available. In a retrospective study we compared the clinical courses of croup caused by influenza and parainfluenza viruses in hospitalized children. By several indicators the clinical picture of croup caused by influenza viruses was significantly more severe than that caused by parainfluenza viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 13 publications
2
31
0
1
Order By: Relevance
“…Although laryngitis associated with influenza was also a relatively infrequent finding in our study, the clinical presentation of croup caused by influenza viruses is much more severe than that caused by parainfluenza viruses. 33 Influenza viruses are among the leading respiratory viruses predisposing a child to acute otitis media. 3,4,8,9,34 In our study, 19% of children Ͻ3 years of age had acute otitis media at their first visit to the study clinic for influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Although laryngitis associated with influenza was also a relatively infrequent finding in our study, the clinical presentation of croup caused by influenza viruses is much more severe than that caused by parainfluenza viruses. 33 Influenza viruses are among the leading respiratory viruses predisposing a child to acute otitis media. 3,4,8,9,34 In our study, 19% of children Ͻ3 years of age had acute otitis media at their first visit to the study clinic for influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer cases of croup are caused by influenza viruses than by parainfluenza viruses [28]. However, croup may be clinically more severe in children with influenza infection than in those with parainfluenza virus infection [40]. Influenza A virus also has been recognized as an important agent that predisposes patients to bacterial tracheitis [41].…”
Section: Discussionmentioning
confidence: 99%
“…RSV, influenza A and B viruses, adenoviruses, rhinoviruses, and, in school age children, Mycoplasma have all been shown to cause croup. A recent retrospective review suggested that influenza virus croup was more severe than parainfluenza virus croup (284).…”
Section: Clinical Syndromesmentioning
confidence: 99%